Nearshore microfossil assemblages in a Caribbean reef environment show variable rates of recovery following Hurricane Irma. Issue 3 (28th October 2021) - Mitchell, Stephen; Pilarczyk, Jessica E.; Spiske, Michaela; Jaffe, Bruce
Abstract: Modern microfossil distributions reflect site‐specific habitats and provide an opportunity to assess sediment transport pathways in the nearshore environment. When applied to overwash deposits in the geological record, they provide insight into sediment provenance and transport, factors important for understanding patterns of frequency and intensity of past storms and tsunamis. Modern distribution studies are rare and often the first established ones occur immediately after an overwash event as part of a post‐event field survey. This is problematic because it is unclear what effect overwash events have on nearshore microfossil assemblages and what time interval is necessary for them to return to pre‐event conditions. This study documents the impacts of Hurricane Irma on nearshore sediments off the coast of Anegada, British Virgin Islands, using distributions of Homotrema rubrum, an encrusting foraminifer with a defined provenance in coral reefs. At four sampling intervals spanning two years, from six months pre‐Hurricane Irma to eighteen months after, surface sediment was collected from three transects on the northern and southern shores of the island. Partitioning Around Medoids cluster analysis revealed that Hurricane Irma introduced an influx of well‐preserved fragments into the reef flat and made the sediments more uniform, limiting the foraminifer's utility as a known sediment transport indicator. The mixing of sediments along the two northern transects (reef proximal) persisted for seven to eighteen months before returning to near pre‐hurricane conditions. However, the southern transect (absence of reef), where Homotrema rubrum concentrations are significantly less, failed to recover within the time period assessed by this study, indicating a variable recovery period between Atlantic Ocean and Caribbean Sea facing shorelines. Results from this study suggest that a waiting period of at least eighteen months after a major storm is recommended before collecting surface sediment from the nearshore environments of reef‐dominated coastlines.